Differential Survivability of Two Genetically Similar Salmonella Thompson Strains on Pre-harvest Sweet Basil (Ocimum basilicum) Leaves - Zwe, Ye Htut; Ten, Michelle Mei Zhen; Pang, Xinyi; Wong, Chun Hong; Li, Dan (Frontiers in Microbiology, 2021)
Although conventionally considered an animal pathogen, recent evidence increasingly suggests that fresh produce may act as significant transmission vehicles and alternative hosts to Salmonella. This study reports the differential survivability of two genetically similar Salmonella Thompson strains (ST 889B and ST 688C) on the adaxial surface of pre-harvest basil (Ocimum basilicum) leaves. Upon inoculation, two distinct phenomena, a dried water-print or a macroscopic lesion, were observed within 24 h. ST 889B survived better than ST 688C on healthy leaves without lesions, possibly due to its higher biofilm-forming ability. Both strains survived better on the leaves with lesions than on the healthy leaves (ST 688C: 4.39 ± 0.68 v. 2.18 ± 0.29; ST 889B: 4.78 ± 0.12 v. 2.83 ± 0.18 log CFU per sample at 6 days post-inoculation). ST 889B caused the formation of lesions at a higher frequency (70/117 leaves [59.8%]) than ST 688C (35/96 leaves [36.5%]). Thus, we highlighted two distinct Salmonella survival strategies in the basil pathosystem and demonstrated gene expression polymorphism (variations in the expression of the same set of genes) as an indispensable strategy in the colonization of plants as hosts by the human pathogens.